The role of pembrolizumab in the treatment of PD-L1 expressing gastric and gastroesophageal junction adenocarcinoma. (August 2019) - Brar, Gagandeep; Shah, Manish A.
Gastric cancer is a leading cause of cancer-related death worldwide. Recent evidence suggests that gastric cancer is a complex and heterogenous disease with emerging subtypes shown to affect response to treatment and survival. Immunotherapy is an advancing field and immune checkpoint inhibitors have become standard treatment options in numerous tumor types. In this review, we discuss the current and evolving use of checkpoint blockade, focusing on the anti-PD-1 inhibitor, pembrolizumab, for use in advanced gastric and gastroesophageal cancers.